Use of social media in nursing education in Saudi Arabia. (2022) - AL-Dossary, Reem N.; Al-Motawa, Tahany Essa; Alanezi, Fahad; Al-Rayes, Saja; Attar, Razaz; Saraireh, Linah; Saadah, Amjad; Alenazi, Naif; Alameri, Rana; Alanezi, Nouf; Alanzi, Turki M.
Abstract: Purpose: The objective of this study was to investigate the use of social media in nursing education in Saudi Arabia. Method: ology: A cross-sectional quantitative study was conducted to investigate the use of social media in nursing education in Saudi Arabia. Google Forms was used to design the survey questionnaire and collect the information from the participants. The questionnaire was initially distributed to 300 nurses belonging to WhatsApp groups from the Eastern Province of Saudi Arabia. 104 participants responded to the questionnaire. The response rate was 34.7%. Results: According to the findings, YouTube was the most used social media for nursing education in Saudi Arabia (46.2%). Also, most of the respondents thought that social media platforms facilitate learning for nurses (87.5%) and can be used to share and discuss materials with educational content (91.3%). Likewise, the participants used social media to access educational courses (81.7%), observe videos with educational information (84.6%), follow pages and profiles regarding nursing education (61.5%), and find blogs and articles with educational topics (74.0%). Most of the participants (78.2%) considered that the educational content found on social media platforms was useful for nursing education. Alike, more than half of the respondents believed that the educational content obtained from social media was reliable, stimulating creative innovation and ideas regarding training and nursing learning. 70.2% of the participants had no problem finding articles, blogs, or any type of information on topics related to nursing education. Conclusion: The results of this research suggest that most of the participants considered that social networks are fundamental tools for the training and education of nurses because they offer new alternatives for the acquisition of the theoretical and practical knowledge of this profession. In this sense, due to the high penetration of social networks in Saudi Arabia, there is the possibility that these tools can be used effectively to improve the educational training of nurses, which will contribute to the promotion of the health of the Arab people.